Concentrations and health risks of metal elements in ambient air PM2.5 in two urban districts of Hefei city from 2015 to 2023: analysis of monitoring data - Yu ZHU; Linling YU; Derui YAN; Changchun XIAO (Zhongguo gonggong weisheng)
ObjectiveTo analyze the concentrations and chronic health risks of metal elements in ambient air particulate matter less than 2.5 microns in aerodynamic diameter (PM2.5) in two districts of Hefei city, Anhui province, from 2015 to 2023. MethodsMonthly 7-day continuous sampling of ambient air PM2.5 was conducted from 2015 to 2023 at two monitoring sites in Baohe district and Yaohai district in Hefei city, and 12 metal elements (including antimony, aluminum, arsenic, beryllium, cadmium, chromium, mercury, lead, manganese, nickel, selenium, and thallium) in PM2.5 were measured. The concentrations and spatiotemporal distributions of these elements were analyzed, and the chronic health risks associated with the metal elements via inhalation were assessed according to the National Health Commission′s Technical Guidelines for Environmental Health Risk Assessment of Chemical Substances (WS/T 777 – 2021). ResultsA total of 1 522 valid filter samples were collected in the two districts of the city during the period. The concentrations of aluminum, selenium, and antimony in the PM2.5 samples collected in Yaohai district were higher than those in Baohe district (Zaluminum = – 3.505, Paluminum < 0.001; Zselenium = – 2.148, Pselenium = 0.032; Zantimony = – 4.919, Pantimony < 0.001), while the differences in the concentrations of other metal elements between the two districts were not significant (P > 0.05 for all). The annual average concentrations of antimony, arsenic, cadmium, lead, selenium, and thallium in the two districts gradually decreased over the years, while aluminum first decreased and then increased. Seasonally, the heavy metal concentrations were highest in winter, followed by the concentrations in spring, autumn, and summer. The median hazard quotients (HQ) of non-carcinogenic risk for all metals in both districts were less than 1. However, 1% to 9% of the HQ values for arsenic, beryllium, cadmium, and manganese were greater than 1, indicating a certain level of non-carcinogenic risk associated with the metals. Six metal elements, including arsenic, beryllium, cadmium, chromium, lead, and nickel posed carcinogenic risks. Among them, 1% to 29% of the carcinogenic risk (CR) values for beryllium, cadmium, lead, and nickel were in the range of 1 × 10 – 6 to 1 × 10 – 4. All the CR values for arsenic and chromium exceeded 1 × 10 – 6, with 1% of the arsenic and chromium in Baohe district and arsenic in Yaohai district exceeding 1 × 10 – 4, indicating a higher carcinogenic risk. ConclusionThe concentrations of metal elements in ambient air PM2.5 in the two districts of Hefei city were highest in winter, with relatively higher concentrations of aluminum, lead, manganese, and arsenic. Arsenic and manganese were the main contributors to non-carcinogenic risk, while arsenic and chromium were the main contributors to carcinogenic risk.